Carbopol 940 hydrogel containing curcumin-loaded micelles for skin delivery and application in inflammation treatment and wound healing. (2nd February 2022) - Song, Zhimei; Wen, Yi; Teng, Fangfang; Wang, Min; Liu, Na; Feng, Runliang
Abstract : Inflammation and excessive reactive oxygen species production are the main reason for slow wound healing, which necessitates an efficient therapy in clinic. Abstract : Inflammation and excessive reactive oxygen species production are the main reason for slow wound healing, which necessitates an efficient therapy in clinic. In the present study, curcumin-enveloped methoxy poly(ethylene glycol)–poly(δ-valerolactone)–poly(ε-caprolactone) (MPEG–PVL–PCL) micelles were prepared and embedded into Carbopol 940 hydrogel for full thickness dermal wound therapy. It was found that the prepared hybrid hydrogel had acceptable skin deposition and permeation, high antioxidant activity, and continuous erosion with sustained curcumin release. In the mouse ear edema model, when induced by croton oil, the anti-inflammatory activity of the hydrogel was better than that of dexamethasone sodium phosphate cream. An in vivo full thickness wound model in Kunming mice was established to evaluate the wound healing effect of the hydrogel. Wound closure, hydroxyproline/DNA content, and histological studies confirmed that the curcumin micelles-embedded hydrogel could promote collagen enrichment and improve re-epithelialization of the epidermis at the wound site. In summary, the curcumin-loaded MPEG–PVL–PCL micelles-embedded Carbopol 940 hydrogel was demonstrated to be a potential candidate for the treatment of skin inflammation and full thickness wound healing.